Soft Magnetic Composites in Novel Designs of Electrical Traction Machines - Zhang, Bo (KIT Scientific Publishing, 2017)
Nowadays, the manufacturing of electrical machines based on electrical steel laminations has been well established worldwide. Compared with the electrical steel, the soft magnetic composites (SMC) shows magnetic isotropy and lower eddy current losses. Thus, it becomes an important impulse promoting the development of new topologies of electrical machine. The application of SMC in the electrical traction machine for hybrid electrical vehicle or electrical vehicle has been researched in the work.